2003
DOI: 10.1182/blood-2003-05-1391
|View full text |Cite
|
Sign up to set email alerts
|

Multiple integrin-ligand interactions synergize in shear-resistant platelet adhesion at sites of arterial injury in vivo

Abstract: Damage to the integrity of the vessel wall results in exposure of the subendothelial extracellular matrix (ECM), which triggers integrin-dependent adhesion and aggregation of platelets. The role of platelet ␤1 integrins in these processes remains mostly undefined. Here, we demonstrate by intravital fluorescence microscopy that platelet adhesion and thrombus growth on the exposed ECM of the injured carotid artery is not significantly altered in ␣2-null mice and even in mice with a Cre/loxP-mediated loss of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 51 publications
11
104
0
4
Order By: Relevance
“…This finding may explain the lack of a major phenotype for collagen receptor glycoprotein VI and integrin a2b1 deficiency observed in some studies. 7,17,18 However, for reasons that remain unclear, other investigators also have reported a severe thrombotic defect for glycoprotein VI deficiency in this model. 13,19 Although they express multiple adhesion molecules, RBCs are not believed to be able to adhere to any other cell types under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…This finding may explain the lack of a major phenotype for collagen receptor glycoprotein VI and integrin a2b1 deficiency observed in some studies. 7,17,18 However, for reasons that remain unclear, other investigators also have reported a severe thrombotic defect for glycoprotein VI deficiency in this model. 13,19 Although they express multiple adhesion molecules, RBCs are not believed to be able to adhere to any other cell types under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…30 Mice deficient in α2 or β1 have normal bleeding times, and display minor defects on platelet adhesion and aggregation to collagen. 31,32 Studies of experimental in vivo arterial thrombosis in these mice have led to conflicting results showing both unaltered formation of thrombi 32 and mildly delayed, reduced and unstable thrombi. 33,34 Like other integrins, conformational activation of α2β1 increases its affinity for collagen, and seems to require inside-out signaling events that might be driven by engagement of GP VI with collagen 23 and/or by activation of αIIbβ3.…”
Section: Initiation Phasementioning
confidence: 99%
“…3; Table 2). [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Integrins can be divided into four subfamilies based on their ligand specificity and/or phylogenetic comparison of the a subunits (Fig. 3).…”
Section: 41mentioning
confidence: 99%